Gadolinium-Encapsulating Iron Oxide Nanoprobe as Activatable NMR/MRI Contrast Agent - Santra, Santimukul (2012)
Herein we report a novel gadolinium-encapsulating iron oxide nanoparticle-based activatable NMR/MRI nanoprobe. In our design, Gd-DTPA is encapsulated within the polyacrylic acid (PAA) polymer coating of a superparamagnetic iron oxide nanoparticle (IO-PAA) yielding a composite magnetic nanoprobe (IO-PAA-Gd-DTPA) with quenched longitudinal spin-lattice magnetic relaxation (T(1)). Upon release of the Gd-DTPA complex from the nanoprobe's polymeric coating in acidic media, an increase in the T(1) relaxation rate (1/T(1)) of the composite magnetic nanoprobe was observed, indicating a dequenching of the nanoprobe with a corresponding increase in the T(1)-weighted MRI signal. When a folate-conjugated nanoprobe was incubated in HeLa cells, a cancer cell line overexpressing folate receptors, an increase in the 1/T(1) signal was observed. This result suggests that upon receptor-mediated internalization, the composite magnetic nanoprobe degraded within the cell's lysosome acidic (pH = 5.0) environment, resulting in an intracellular release of Gd-DTPA complex with subsequent T(1) activation. No change in T(1) was observed when the Gd-DTPA complex was chemically conjugated on the surface of the nanoparticle's polymeric coating or when encapsulated in the polymeric coating of a non-magnetic nanoparticle. These results confirmed that the observed (T(1)) quenching of the composite magnetic nanoprobe is due to the encapsulation and close proximity of the Gd ion to the nanoparticles superparamagnetic iron oxide (IO) core. In addition, when an anticancer drug (Taxol) was co-encapsulated with the Gd-DTPA within the folate receptor targeting composite magnetic nanoprobe, the T(1) activation of the probe coincide with the rate of drug release and corresponding cytotoxic effect in cell culture studies. Taken together, these results suggest that our activatable T(1) nanoagent could be of great importance for the detection of acidic tumors and assessment of drug targeting and release by MRI.